EFEKTIVITAS PENGOLAHAN SAMPAH DI PUSAT DAUR ULANG MENGWITANI - Nada, I Made; Satya Graha, I Made; Wahyu Wijaya, I Made; Intan Yuni Antari, Ni Kadek (Jurnal Ecocentrism, 2024)
One of the issues arising from the increasing population every year, along with the increase in activities and consumption of residents in Mengwi District, is the increase in waste generation. The purpose of this study is to determine the effectiveness of waste management at the Mengwitani Recycling Center (PDU). This research uses a quantitative method, where the effectiveness measurement is conducted through the inventory of waste processing units at the Mengwitani Recycling Center (PDU). The inventory data is used to compile the mass balance of the waste entering and exiting each processing unit for data analysis in determining the effectiveness of waste management at the Mengwitani Recycling Center (PDU). The effectiveness of waste management at the Mengwitani Recycling Center (PDU) was determined by the total waste intake over a year from June 2023 to June 2024, which reached 236,911.18 kg. Of this, the total wet organic waste amounted to 219.53 kg, and inorganic waste to 2,086.11 kg. The total residue reached 233,999.62 kg, with 233,999.62 kg of waste being incinerated. The incinerated waste produced 73,905.33 kg of ash, resulting in an average total waste reduction percentage at the Mengwitani PDU over one year of 70.14%.